Petani Kopi Mensiasasi Perubahan Iklim - Mochamad Widjanarko; Farida Yuliani; Adinda Amelia Fitriani (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to determine the level of knowledge, perceptions of impacts, and adaptation strategies of farmers in Japan Village, Kudus Regency, in coping with climate change. The study employed a descriptive quantitative method involving 25 farmers as respondents through total sampling. Data were collected using closed-ended and open-ended questionnaires and analyzed using descriptive percentage analysis. The results indicate that farmers’ knowledge of climate change in Japan Village, Kudus Regency, remains relatively low at a conceptual level but is strong in terms of observations based on local experience. This is evident in farmers’ ability to recognize environmental changes through biological indicators, such as the condition of coffee plants, shifts in seasonal patterns, and other natural signs, compared to their ability to explain climate change concepts scientifically. Most farmers do not receive adequate information support from government institutions in addressing climate change. The adaptation strategies employed by coffee farmers in Japan Village to interpret climate conditions rely heavily on personal experience, the “titen” method (analysis based on customary patterns), and traditional knowledge passed down from their parents. Although the sample size is relatively small (25 farmers), this study offers a deep perspective on the unique local wisdom of the Muria foothills region in responding to climate change.